Research and application of air-to-ground continuous coverage technology for air-space emergency communication system - Shengwei CHEN; Fan LI; Guangping YANG; Jian ZHOU; Yu SU (Dianxin kexue)
To solve the problem of small coverage area and discontinuous coverage of large fixed-wing aerospace emergency base stations, a design scheme for continuous coverage of UAV emergency base stations was proposed.Based on the analysis of the coverage capability of the single antenna of the airborne base station, a multi-antenna coverage scheme with inner antenna plus edge antenna was proposed.Taking the roll angle, pitch angle and other parameters of the UAV flight into consideration, the installation plan of multi-antenna mounting that guarantees continuous coverage was designed.Then the link budget was carried out according to the 3GPP propagation loss model, and the UAV flight plan was planned according to the continuous coverage area requirements.Simulation and flight test results show that the proposed scheme can achieve 50 km2 continuous signal coverage of the ground by the mobile base station on the UAV without using the intelligent control of the antenna angle of the PTZ.